Рецидивний папілярний рак щитоподібної залози: клініко-морфологічні особливості - Ларін, О. С.; Хоперія, В. Г.; Гузь, О. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
In a retrospective study clinicopathological parameters predicting recurrence were determined by retrospective analysis of 21 patients with recurrent papillary thyroid carcinoma, followed for 6 to 64 months with median follow up of 22,24 months after treatment of primary papillary carcinoma of the thyroid, the authors searched for possible prognostic factors of the risk of recurrence. Because papillary thyroid carcinoma is associated with an excellent prognosis after surgical removal, large numbers of patients with extremely long term follow up are needed to identify the clinical relevance of factors prognostic for recurrence. In contrast, we recruited only a relatively small number of eligible patients with recurrent papillary thyroid carcinoma, and the median follow up period was short. The lack of association between previously determined prognostic factors and clinical recurrence in this study may have resulted from these limitations in sample size and follow up duration. Selection of proper management strategies for individual patients should be based on the results of longer term follow up studies with larger numbers of patients.